Analisis Produksi Padi di Sumatera Utara - Mahara Sintong; Muhammad Miftahurridlo; Rohil Al Azizah; Adelina Lumbantobing; Rafa Aurifa Maruhawa; Akilah Nurhalifah; Rahmi Rahmi; Arfiah Wulandari Mandailing (CV. PUSDIKRA MITRA JAYA, 2025)
This study analyzes rice production trends in North Sumatra from 2020 to 2024 by examining fluctuations, key influencing factors, and their statistical significance. Using quantitative methods with descriptive statistics and multiple linear regression, the research utilizes secondary data from the Central Bureau of Statistics (BPS). The results show a consistent increase in rice production from 4.51 million tons in 2020 to 5 million tons in 2024, supported by growth in harvested area, fertilizer use, and seed utilization. Regression analysis reveals that harvested area, fertilizer, and seed quantities significantly influence production, while labor input is not statistically significant. Climate variability, land conversion, and limited adoption of modern agricultural technology remain key challenges. This study highlights the urgency for improved irrigation, technology adoption, and equitable subsidy distribution to support long-term production stability.